2019
DOI: 10.1002/jcop.22218
|View full text |Cite
|
Sign up to set email alerts
|

A house is not a home: Modeling the effects of social support and connection within resettled refugee populations

Abstract: Aim The U.S. resettlement program currently resettles refugees in communities of similar or the same ethnic background known as like‐ethnic communities. This practice provides resettled refugees with a familiar community who may be able to provide support through the difficult resettlement process. However, by associating with a like‐ethnic community, resettled refugees may limit interaction with the host community, which may have subsequent adverse effects on well‐being. Methods This study examined whether sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…These contrasting results are probably due to the fact that most of these studies do not address gender differences. Furthermore, Latin American women may find it easier to adapt to Spanish society because of shared language and values (Wanna, Seehuus, Mazzulla, & Fondacaro, 2019). They may also value contact with neighbours and the community (Maya‐Jariego, Holgado, Márquez, & Santolaya, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These contrasting results are probably due to the fact that most of these studies do not address gender differences. Furthermore, Latin American women may find it easier to adapt to Spanish society because of shared language and values (Wanna, Seehuus, Mazzulla, & Fondacaro, 2019). They may also value contact with neighbours and the community (Maya‐Jariego, Holgado, Márquez, & Santolaya, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the participant's history of torture severity was calculated by a sum of the experiences of torture endorsed in the part I of the HTQ. Events reported as "witnessed' or "heard about" were not included within torture severity to be consistent with existing literature on similar studies which utilised the HTQ (e.g., Arnetz et al, 2014;Wanna et al, 2019). For the PTSD variable in this study, the mean score of trauma symptoms reported by the participant on the part (IV) of the HTQ was used, as guided by the scoring manual.…”
Section: Methodsmentioning
confidence: 99%
“…Seventy percent of the studies that used psychological well-being were measured within a medical framework, primarily through standardised clinical survey instruments such as the Hopkins Symptom Checklist (HSCL-25) [25][26][27][28]. The HSCL-25, a symptom inventory focused specifically on anxiety and depression, comprises 25 items divided into two parts: 10 assessing anxiety symptoms and 15 assessing depression symptoms.…”
Section: Well-being Outcomesmentioning
confidence: 99%